Clinician's Guide to Medical Writing - Taylor, Robert B. (Springer New York : Imprint: Springer, 2005)
This book teaches what clinicians need to know about medical writing and publishing. It is for the physician, physician assistant, or nurse practitioner who sees patients and also wants to contribute to the medical literature, as well as for the assistant professor aspiring to promotion. It is written from the viewpoint of the clinician seeking the personal enrichment that writing can bring. Readers learn how to translate observations and ideas from practice into written form and eventually into print. The guide for this journey is Dr. Robert B. Taylor, a distinguished leader in academic family medicine. With a clear, conversational writing style, Dr. Taylor shares what he has learned-what works and what doesn't-through the course of publishing 22 medical books and several hundred papers. He draws from his successes (and some failures) as he tells helpful ways to write review articles, case reports, editorials, letters to the editor, book reviews, book chapters, reference books, and research reports. Loaded with practical advice and real-world examples, this text benefits readers who are new to medical writing and those who have authored a few articles or chapters and want to improve their skills.